2009
DOI: 10.1128/jcm.01183-08
|View full text |Cite
|
Sign up to set email alerts
|

Borrelia carolinensissp. nov., a New (14th) Member of theBorrelia burgdorferiSensu Lato Complex from the Southeastern Region of the United States

Abstract: Approximately 118 Borrelia isolates were cultured from a variety of rodents, birds, and ticks collected in the southern United States. In addition to a highly diverse group of Borrelia bissettii strains and a homogenous group of Borrelia burgdorferi sensu stricto strains, a group of 16 isolates with unusual characteristics was found. The isolates were cultured from ear biopsy samples of the rodents Peromyscus gossypinus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
91
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(91 citation statements)
references
References 52 publications
(29 reference statements)
0
91
0
Order By: Relevance
“…genospecies identification, we performed an in silico restriction fragment length polymorphism analysis and a 'virtual hybridization' [47].…”
Section: Apathya Cappadocicamentioning
confidence: 99%
“…genospecies identification, we performed an in silico restriction fragment length polymorphism analysis and a 'virtual hybridization' [47].…”
Section: Apathya Cappadocicamentioning
confidence: 99%
“…The results with flaB have shown only minor differences among relapsing fever Borrelia species. On the other hand, although the intergenic spacer rrs-rrl is not able to discriminate between B. recurrentis and B. duttonii (29), it has been shown to discriminate between strains of other RF Borrelia species.Multilocus sequence analysis (MLSA) is a powerful tool for the delineation of species and assignment of strains to defined species (23,25,26). The utilization of this method is increasing, especially with uncultured and slow-growing organisms that cannot be analyzed by DNA-DNA hybridization.…”
mentioning
confidence: 99%
“…Its etiologic agent, Borrelia burgdorferi sensu lato, was originally thought to be homogeneous. However, many studies have demonstrated that B. burgdorferi sensu lato is phenotypically and genotypically heterogeneous (13,14,21 (2,5,8,10,11,20).…”
mentioning
confidence: 99%